New species of the genera Draconema Cobb, 1913 and Paradraconema Allen & Noffsinger, 1978 (Nematoda: Draconematidae) from the Andaman Islands, Indian Ocean, with keys to the species - Kito, Kenji; Chatterjee, Tapas (Zootaxa, 2012)
Two new species of Family Draconematidae Filipjev, 1918, Draconema andamanense sp. nov. and Paradraconemapachylumbus sp. nov., are described from the coast of the Andaman Islands, India. Both species were extracted from sed-iments among the intertidal macroalgae. Draconema andamanense resembles D. japonicum in having the gubernaculumwith peculiar distal dilation in males. However, it differs from all the congeneric species including D. japonicum by thesmaller number of subventral adhesion tubes (10–11 in male and 12–14 in female). Paradraconema pachylumbus differsfrom all the congeneric species by having the cloacal region remarkably enlarged towards the dorsal side and the conico-cylindrical tail abruptly narrowing. Paradraconema pachylumbus most resembles P. floridense with longitudinally areo-lated annules, elongate loop-shaped amphids, prominent eyespots, subventral precloacal Acan-set and gubernaculum withlateral dilation, but is distinguishable from it by the number of setae on the tail in males and females, and the gubernaculum length and tail length in males, as well as the peculiar feature of an enlarged cloacal region in males.